The Impact on Family Functioning of Social Media Use by Depressed Adolescents: A Qualitative Analysis of the Family Options Study - Lewis, Andrew J.; Knight, Tess; Germanov, Galit; Benstead, Michelle Lisa; Joseph, Claire Ingrid; Poole, Lucinda (Frontiers in Psychiatry, 2015)
Background: Adolescent depression is a prevalent mental health problem, which can have a major impact on family cohesion. In such circumstances, excessive use of the Internet by adolescents may exacerbate family conflict and lack of cohesion. The current study aims to explore these patterns within an intervention study for depressed adolescents. Method: The current study draws upon data collected within the Family Options randomized controlled trial that examined family-based interventions for adolescent depression (12-18 years old) in Melbourne (2012-2014). Inclusion in the trial required meeting diagnosis for a Major depressive disorder via the Structured Clinical Interview for DSM-IV Childhood Disorders (KID-SCID). The transcripts of sessions from 7 group treatments were examined using qualitative thematic analysis. The transcribed sessions consisted of 56 hours of recordings in total from 39 parents who took part in the interventions. Results: The thematic analysis explored parental perceptions of their adolescent’s use of social media and access to Internet content, focusing on the possible relationship between adolescent Internet use and the adolescent’s depressive disorder. Two overarching themes emerged: The sense of loss of parental control over the family environment, and parents’ perceived inability to protect their adolescent from material encountered on the Internet and social interactions via social media. Conclusions: The excessive use of social media often interacted with cyber-bullying and altered the adolescent’s understanding of friendship. Parents within the context of family based treatments felt that prolonged exposure to social media exposed their already vulnerable child to cyber-bullying. The thematic analysis uncovered a sense of parental despair and lack of control, which is consistent with their perception of social media and the internet as relentless and threatening to their parental authority and family cohesion.